Lifting the veil: pyrogeographic manipulation and the leveraging of environmental change by people across the Vale of Belvoir, Tasmania, Australia - Fletcher, Michael-Shawn; Romano, Anthony; Nichols, Scott; Henriquez Gonzalez, William; Mariani, Michela; Jaganjac, Diana; Sculthorpe, Andry (Frontiers in Environmental Archaeology, 2024)
Humans undertake land management and care of landscapes to maintain safe, healthy, productive and predictable environments. Often, this is achieved through creating spatial and temporal heterogeneity in a way that leverages the natural world; both amplifying natural trends and, in some cases, driving shifts counter to natural processes. However, a persistent paradigm governing the understanding of proxy evidence of past human activity on the environment is that human agency is only recognised in proxy data when trends oppose what are expected to occur naturally. Framing research in such a way ignores the fact that people have, continue to, and will always leverage the environment in ways that both compliment and diverge from "natural" trends. Doing so masks, or erases, people from the histories of their territories and continues to perpetuate myths such as "wild" and "wilderness", particularly in places that have in fact been shaped and maintained by people for long periods of time. Here, we synthesise geographical, dendrochronological, palaeoecological, archaeological and palaeoclimatic data to demonstrate how Palawa people (Tasmanian Aboriginal people) in Lutruwita (now known as Tasmania, southeast Australia) leveraged climatic change to convert unproductive forest vegetation to open forest and grassland to support higher occupation levels. The fine-scale heterogeneity we have identified reflects the diversity of ways in which, and the spatial scale that, the Palawa engage with their land. We caution against adopting coarse spatial scale (i.e., continental, regional, etc.) methodologies to reconstruct the influence of past societies over landscape evolution as they assume homogeneity of human cultures and of human influence on landscapes. We also reinforce calls for those researching past landscape change to abandon tropes of human agency acting only in opposition to the natural world. Such approaches are couched within a narrow cultural understanding of human-environment interactions and result in the erasure of Indigenous and local peoples' role in maintaining healthy, biodiverse and safe landscapes.